Commodity prices: Structural factors, financial markets and non-linear dynamics - Diego Bastourre; Jorge Carrera; Javier Ibarlucia (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2010)
Up to the financial slump of the second quarter of 2008 commodity prices grew fast for several consecutive years in a highly volatile context. Recent commodity fluctuations have raised both policy concerns and a prolific academic debate. This paper offers a coherent theoretical and empirical framework aimed at improving our knowledge of those elements driving commodity prices in the long run once the so-called process of financialization of commodities is incorporated into the analysis. To this end, we employ a smooth transition vector autoregressive model which is suitable for testing the hypothesis derived from a heterogeneous agent model in the commodity markets. The empirical methodology allows us to distinguish among those variables that influence prices in the long run - obtaining in this way an equilibrium or fundamental price; and the mechanisms that generate, strengthen and eventually correct short run deviations with respect to that equilibrium. The results suggest that high discrepancies between spot and fundamental prices tend to be corrected relatively fast, while small misalignments tend to persist over time without any endogenous correcting force taking place.
Keywords: C32; D84; Q11; 330; commodity prices; developing countries; financial markets; non-linear dynamics; Rohstoffpreis; Finanzmarkt